مشروعية التحفظ على المعاهدات الدولية لحقوق الإنسان - عبو، توركية (جامعة سعيدة الدكتور مولاى الطاهر - كلية الحقوق والعلوم السياسية - مخبر حماية حقوق الانسان بين النصوص الدولية والنصوص الوطنية وواقعها في الجزائر, 2024)
يعد نظام التحفظ على الاتفاقيات الدولية أحد المظاهر القانونية الحديثة في مجال العلاقات الدولية، الذي يقضي بحق الدول بإبداء التحفظ على بعض أحكام الاتفاقيات الدولية طبقا للأحكام العامة التي حددتها المواد (19 -23) من اتفاقية فيينا لقانون المعاهدات 1969، إذ بموجبه يجوز لبعض الدول استثناء بعض نصوص الاتفاقية الدولية من التطبيق بالنظر لطبيعة كل دولة وظروفها الداخلية، وإذا كان حق الدول بالتحفظ مكفولا دوليا، فإن الإشكالية القانونية تكمن في تلك التحفظات التي تبديها بعض الدول على أحد بنود الاتفاقيات الدولية المتعلقة بحقوق الإنسان، ولا شك إن إبداء التحفظ على تلك الاتفاقيات قد يسهم في تجزئة النظام الاتفاقي المزمع إرسائه أو وقف الآثار القانونية لبعض القواعد الدولية المتعلقة بحقوق الإنسان في مواجهة الدول المتحفظة، وبالنظر لأهمية الموضوع ارتأيت أن ابحث بهذا المضمار مبينا المقصود بالتحفظات الدولية على اتفاقيات حقوق الإنسان ومدى مشروعيتها ثم اعرض أهم الإجراءات القانونية الخاصة بها وسبل الرقابة عليها The system reservation to international conventions is one of modern legal appearances in international relations, under which the States have right to express its reservation on some provisions of the international conventions in accordance with the general rules set by the material (-) of the Vienna Convention on the Law of Treaties, It is hereby permitted to some Contracting States exclude some provisions of the International Convention of the application in view of of the nature and circumstances of each country's internal. Considering the right of States to use a means of the reservation is guaranteed internationally, the problem lies in those legal reservations made by some countries to one of the materials the international conventions on human rights. without a doubt a reservation on those conventions may contribute to the fragmentation conventional system which planned docking or to stop the legal effect of international rules concerning human rights in face reserving states. Of the importance of this topic I thought to look for in this regard, to show intended reservations international conventions human rights and the its legitimacy then show their own legal procedures and ways Oversight
Keywords: القانون الدولي -- المعاهدات الدولية -- نظام التحفظ -- العلاقات الدولية